NATIONALITY SECURITY OF THE REPUBLIC OF UZBEKISTAN ISSUES OF DEVELOPMENT AND ADOPTION FOR IMPLEMENTATION OF THE CONCEPT OF INFORMATION SECURITY OF THE REPUBLIC OF UZBEKISTAN - Danchenkov Valentin Ivanovich (American Journals Publishing, 2023)
The author in this article pays attention to the issue of protecting the national security of the Republic of Uzbekistan in the information sphere. As a result of the conducted research, the main elements of the Information Security Concept of the Republic of Uzbekistan are identified and formulated.
Keywords: National Security of the Republic of Uzbekistan, the Concept of Information Security of the Republic of Uzbekistan, the Center for Research on Information Security Issues of the Republic of Uzbekistan, the Department of Cyber Law.